ANALISIS PENDAPATAN USAHA TANI BAWANG MERAH DI DESA SUNGAI RUMPUN KECAMATAN GUNUNG TUJUH KABUPATEN KERINCI - Zasriati, Masrida; Sarmigi, Elex (Politeknik Negeri Ambon, 2023)
This study aims to analyze the development of the shallot farmer business based on income and costs incurred. The population of this study were shallot farmers in Kerinci Regency, while the sample for this study were shallot farmers in Sungai Rumpun village as many as 76 respondents. This research approach is descriptive quantitative by analyzing the income and costs incurred by farmers, without examining the causal relationship deeper. The results of this study indicate that the total income of shallot farmers in Sungai Rumpun Village is Rp. 1,291,600,000 with an average of Rp. 16,994,736.84 per harvest season. The total cost is Rp. 688,804,958.33 with an average of IDR 9,063,233.14 per harvest season. The net income of shallot farmers in Sungai Rupun Village per harvest season is Rp. 602,795,041.67 per harvest season with an average of Rp. 7,931,513.71 per harvest season.